France’s plan and the part of the banking system in its drafting and execution - FRADAULT, P. (PSL Quarterly Review, 2014)
<!–[if gte mso 9]> 72 1024x768 <![endif]–> The objective of French economic planning is the drawing up and subsequent execution of a “programme for modernising plant and equipment”. The very importance of the investments to be made and the proper equilibrium to be established between them raise difficult financing problems that necessitate the coordination of decisions. The present article illustrates the importance of the participation of the Bank of France and the banks in French planning as a whole and how this participation takes place in two successive phases. In the preparatory and elaborative phase the central bank and representatives of the banking system cooperate in the work of the chief bodies that have to establish the general lines to be followed in planning. In the executive phase the central bank contributes to decisions of a monetary and financial character. In the various credit operations the banks follow the directives of the monetary authorities and carry out a very important task in examining and granting medium-term loans for equipment. JEL: E52, E58, G21, G28 <!–[if gte mso 9]> Normal 0 14 <![endif]–><!–[if gte mso 10]> <![endif]–>